Participatory Practices in Open Source Educational Software - The Case of the Moodle Bug Tracker Community - Costello, Eamon (School of Education, 2014)
The Moodle bug tracker is a boundary object that faces software developers who write and maintain Moodle’s code whilst simultaneously exposing an interface to a much wider public world of ordinary Moodle users. Bugs can be fixed and new features requested by recording them in this boundary object which then tracks their progress. Such tracking has proven a powerful lure for researchers and despite much study of the phenomenon of open source bug fixing and software building, much remains to be answered. Specifically this research sought to analyse the implications of this massively distributed collaborative development process for education and educational technology (which to give it due importance, is referred to here as educational infrastructure). It examined the ways educators - who are defined inclusively as all those involved in supporting the educational enterprise - interface and contribute to the development of the Virtual Learning Environment (VLE) Moodle at this granular level of bug fixing. Two things happen in a successful bug resolution: it is reported and then it is fixed. Only one population is skilled and empowered to engage in the latter but, in theory, anyone can be a reporter. Here data was collected and analysed about these two types of participant. Firstly archival and statistical analysis of thousands of issues contained in the tracker database itself was undertaken. These canonical accounts of bug-fixing contributed to the design and conduct of interviews of both core participants of this community and more casual or peripheral members. A broad spectrum of community participants were interviewed from fringe and casual members to some of the key actors including Tim Hunt of the Open University, Moodle HQ members Helen Foster and Michael du Raadt and Moodle founder Martin Dougiamas. Ethnographically inspired methods were utilised in the interview analysis to uncover rich stories of actual practice that were absent from the accounts of the database itself. This lead to several contributions to research being made by this thesis: a depiction of the dynamics and characteristics of an open source software community of practice dedicated to the enterprise of education; an enumeration of three complexes of factors leading to bug tracker issue resolution elicited from participants themselves; an account of particular unknown or under-reported non-canonical issue resolution factors; a model of the role of bug tracker issue mediators including the novel brokerage act of proxy issue submission and improvement; and a theory of how bug trackers are resistant to predictive models of issue resolution. These findings have implications for educational institutions reliant on VLEs and for developers of open source educational software
Keywords: Moodle Bug